2012
DOI: 10.1149/2.010201jss
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Graphene Nanoplatelet Composites toward Arsenic Removal

Abstract: Magnetic graphene nanoplatelet composites (MGNCs) decorated with core-shell Fe-Fe 2 O 3 nanoparticles (NPs) have been synthesized using a facile one-pot thermal decomposition method. The graphene nanoplatelets (GNPs) decorated with uniformly dispersed NPs are observed to exhibit a strong magnetization and can be magnetically separated from the liquid mixture by a permanent magnet. These MGNCs demonstrate an effective and efficient adsorption of arsenic(III) in the polluted water due to the increased adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…Typical substrates include low-cost abundant ones, such as naturally occurring minerals [21], activated carbons [22], graphene oxide (GO) [23][24][25][26][27][28][29][30][31][32][33], and cellulose [34], as well as some specially synthesized costly ones, such as mesoporous carbons [35,36], carbon nanotubes [37], macroporous silica [38], etc. Such nanocomposite adsorbents facilitate their more convenient separation following adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Typical substrates include low-cost abundant ones, such as naturally occurring minerals [21], activated carbons [22], graphene oxide (GO) [23][24][25][26][27][28][29][30][31][32][33], and cellulose [34], as well as some specially synthesized costly ones, such as mesoporous carbons [35,36], carbon nanotubes [37], macroporous silica [38], etc. Such nanocomposite adsorbents facilitate their more convenient separation following adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites with GO have attracted great interest due to their unique properties, which are derived from extended interactions between the GO and the matrix and their wide potential applications such as electromagnetic wave shielding and sensors [24][25][26][27][28][29][30][31][32]. For example, Cao et al [33] found that the tensile strength and young's modulus of GO composites increased by 78 and 73%, respectively, when compared with pure polystyrene.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhu et al have developed graphene decorated with core-shell Fe-Fe 2 O 3 nanoparticles which show efficient adsorption capacity for As(III) in polluted water. 38 This method takes advantage of the use of Fe 2 O 3 which increases the total adsorption sites, while the Fe core makes the material magnetically separable. Luo and co-workers expanded further on this work, by showing that the introduction of MnO 2 nanoparticles into a Fe 3 O 4 -rGO material increases the pH range of effective As(III) and As(V) adsorption.…”
Section: Water Remediation By Adsorptionmentioning
confidence: 99%